Sifat fisikokimia marshmallow kulit buah naga merah (Holycereus polyrhizus) dengan perbedaan konsentrasi sari lemon dan gula pasir: Physicochemical properties of red dragon fruit peel marshmallow (Holycereus polyrhizus) with differences in lemon juice and sugar concentrations - Azara, Rima; Budiandari, Rahmah Utami; Sari, Poppy Diana; Maziya, Zidny (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
The red dragon fruit peel (Hylocereus polyrhizus), which is often discarded as waste around 30–35% of the total fruit, has potential as a natural food colorant. One innovative use is as a raw material for marshmallow, a soft, spongy candy typically made from sugar, gelatine, colouring, and flavouring agents. Sugar addition plays a role in sweetness, texture, and appearance enhancement. Additionally, lemon juice can be used as a natural flavour due to its bioactive compounds such as flavonoids, limonoids, and high vitamin C content. This study aims to investigate the effect of different concentrations of granulated sugar and lemon juice on the physicochemical characteristics of marshmallow made from red dragon fruit peel. The study employed a randomized complete block design (RCBD) with two factors: sugar concentration (27%, 35%, 43%) and lemon juice concentration (0.7%, 1.3%, 1.9%) with three replications. Parameters observed included moisture content, ash content, vitamin C, total sugar, whiteness index, and hardness. The results showed no interaction between sugar and lemon juice. Sugar concentration significantly affected moisture content, ash content, total sugar, whiteness index, and hardness of the marshmallow. In contrast, lemon juice concentration did not have a significant effect on all measured parameters. Furthermore, vitamin C content showed no significant differences among treatments.